2010
DOI: 10.1063/1.3488000
|View full text |Cite
|
Sign up to set email alerts
|

Vertical polyelectrolyte-gated organic field-effect transistors

Abstract: Short-channel, vertically structured organic transistors with a polyelectrolyte as gate insulator are demonstrated. The devices are fabricated using low-resolution, self-aligned, and mask-free photolithography. Owing to the use of a polyelectrolyte, our vertical electrolyte-gated organic field-effect transistors (VEGOFETs), with channel lengths of 2.2 and 0.7 μm, operate at voltages below one volt. The VEGOFETs show clear saturation and switch on and off in 200 μs. A vertical geometry to achieve short-transist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…A vertical configuration, where the OS thin film is sandwiched between two (metallic) contacts, is very attractive because the channel length is defined by the thickness of the OS layer, which is very well controllable down to a few nm, whereas the device area is given by the overlap of the contacts1213. Vertical geometries enable the investigation of charge transport in organic semiconductors at the nanoscale.…”
mentioning
confidence: 99%
“…A vertical configuration, where the OS thin film is sandwiched between two (metallic) contacts, is very attractive because the channel length is defined by the thickness of the OS layer, which is very well controllable down to a few nm, whereas the device area is given by the overlap of the contacts1213. Vertical geometries enable the investigation of charge transport in organic semiconductors at the nanoscale.…”
mentioning
confidence: 99%
“…This is characterized by an absent or strongly tilted saturation region in the output curves. [17,18,29] OFETs suffer from short-channel behavior when the contact resistances become comparable to the channel resistance. This is often attributed to an injection barrier (Schottky barrier, [30] or Fermi-level pinning [31,32] ) at the polymerelectrode interface.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach for interrogating single polymers is sketched in Figure 1d,e. We employ pairs of electrodes separated by a ≈10 nm-thick insulator layer to form a vertical OFET (VOFET [16][17][18] ) and immerse this structure in an inert electrolyte. The electrode-insulator-electrode nanogap geometry is readily achieved in microfabricated devices by carefully controlling the thickness of an insulating layer and using the top electrode as a mask in a self-aligned process.…”
Section: Introductionmentioning
confidence: 99%
“…The seminal works on EGOFETs were those from Bäcklund et al [5], Panzer and Frisbie [6] or Crispin, Berggren and coworkers [7,8], who first reported these devices using solid electrolytes (polymer electrolytes or polyelectrolytes). Later, Kergoat et al [9] demonstrated that solid electrolytes could be simply replaced by water.…”
Section: Introductionmentioning
confidence: 99%